Hearing Without Neuroglobin. (16th December 2017) - Nowotny, Manuela; Kiefer, Lenneke; Andre, Daniel; Fabrizius, Andrej; Hankeln, Thomas; Reuss, Stefan
Highlights: Neuroglobin-knockout mice exhibited moderately augmented DPOAE-thresholds. Efferent regulation of outer hair cell activity is impaired in Ngb-knockout mice. Acute effects of noise trauma were similar in Ngb-KO and WT animals. Ngb-KO mice retained higher permanent threshold shifts for tones at trauma frequency. Lack of neuroglobin results in only marginal deficits in hearing ability. Abstract: Neuroglobin (Ngb) is a member of the globin family of respiratory proteins, which was recently observed in many neurons of the auditory pathways. Up to now, however, nothing was known about the role of Ngb in hearing processes. We therefore studied auditory function by recording distortion-product otoacoustic emissions (DPOAE) and auditory brainstem responses (ABRs) in wild-type (C57BL/6N) and Ngb-knockout mice. In KO mice, DPOAE thresholds were moderately augmented in the range of 5–18 kHz, reaching statistical significance at 8 and 10 kHz, while the ABR thresholds were not different between groups. The activation of the efferent system by an additional noise given to the contralateral ear resulted in an increased f 2– f 1-emission level only in WT animals. A noise exposure resulted in similar acute threshold shifts in the DPOAE and ABR of both animal groups. The recovery of hearing function, expressed by decreased DPOAE thresholds, was not significantly different between groups after four days and after four weeks. ABR recordings showed that threshold shifts elicited by noise-trauma were slightly better revised in wild-type mice. While ABR amplitudes were similar in both groups before noise overexposure, four weeks after trauma a moderate but statistically significant decrease of the latest peak-to-peak response amplitude (originating in the inferior colliculus) was observed in KO mice. Our results suggest that the lack of Ngb, at least in the model used in the present study, results in only marginal deficits in hearing ability. A putative functional role of Ngb in the efferent system warrants further studies.